South for the winter? Within‐dive foraging effort reveals the trade‐offs between divergent foraging strategies in a free‐ranging predator. (22nd February 2016) - Arthur, Benjamin; Hindell, Mark; Bester, Marthan N.; Oosthuizen, W. Chris; Wege, Mia; Lea, Mary‐Anne
Summary: Central to an animal's fitness is its foraging strategy and understanding the choices made by foraging animals is a fundamental aim in animal ecology. For diving animals, quantifying foraging effort within dives provides a measure of foraging that can be integrated with location information to reveal how animals use their environment as well as the trade‐offs associated with contrasting foraging strategies. We investigated the diving behaviour of 12 free‐ranging Antarctic fur seals ( Arctocephalus gazella ) during their post‐breeding winter migrations, quantifying within‐dive foraging effort using a novel approach to identify divergent foraging strategies and determine the costs and benefits associated with foraging decisions. Significant differences identified in both diving behaviour and foraging effort of female Antarctic fur seals could be attributed to two main, contrasting foraging strategies. Habitat was a major determinant of diving and foraging behaviour, with clear differences occurring either side of the Polar Front, a prominent oceanographic feature in the Southern Ocean. Longer night duration and improved access to vertically migrating prey lead to increased foraging opportunities and a reduced foraging effort south of the Polar Front. Dives in this region were short and shallow. Conversely, seals remaining closer to the breeding colony north of the Polar Front had deep, long dives and an elevated foraging effort. The distinct foraging strategies of fur seals have associated trade‐offs related to habitat availability, travel costs, prey accessibility and prey quality, which are likely driving their foraging decisions. This study highlights the trade‐offs between contrasting foraging strategies that currently coexist within a population of a wide‐ranging predator and raises questions about the viability of strategies with future change to population size or environmental conditions. Finally, understanding the trade‐offs associated with foraging strategies is important for assessing the foraging decisions of animals across a variety of environments. Abstract : Lay Summary